The Septuagint and legal traditions - Verburg, J (2021)
There are many minor differences between the Masoretic Text of the biblical laws and the Septuagint’s translation. What led the Septuagint’s translators to deviate from the Vorlage? Was it a matter of textual exegesis, development of halakhah, custom among the local Jewish community, or influence of contemporary Egyptian law? This thesis evaluates past scholarship, establishes the meaning of the Septuagint through contemporary texts, and compares the Septuagint to early rabbinic halakhah. This thesis argues that “intermediaries”—i.e., traditions of interpretation that arose between the time of composition and the time of translation—often shaped the translator’s understanding of the biblical laws. This thesis introduces new evidence to support the proposal of influence of Egyptian law on the Septuagint.